2011
DOI: 10.1007/s00586-011-1743-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of a personalized hybrid biomechanical model to assess change in lumbar spine function with a TDR compared to an intact spine

Abstract: Total disc replacements (TDRs) have been employed with increasing frequency in recent years with the intention of restoring natural motion to the spine and reducing adjacent level trauma. Previous assessments of the TDRs have subjectively measured patient satisfaction, evaluated sagittal range of motion via static imaging, or examined biomechanical loading in vitro. This study examined the kinematics and biomechanical loading of the lumbar spine with an intact spine compared to a TDR inserted at L5/S1 in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…It is not merely a joint which connects two moving parts. The intervertebral disc, especially in the lumbar region, serves to resist motion and reduce stress concentrations in the adjacent level tissue [4,9].…”
Section: Mechanical Responsementioning
confidence: 99%
See 3 more Smart Citations
“…It is not merely a joint which connects two moving parts. The intervertebral disc, especially in the lumbar region, serves to resist motion and reduce stress concentrations in the adjacent level tissue [4,9].…”
Section: Mechanical Responsementioning
confidence: 99%
“…Ball and socket bearings to not completely replicate the functions of the natural IVD. These bearings tend to be axially rigid and are not designed to resist bending or rotational moments, allowing motion to occur in excess of that permitted by the natural disc [9,80]. These qualities can lead to changes in range of motion (ROM), segmental lordosis, or facet stressing [3,15,26,[81][82][83].…”
Section: (A) Ball-and-socket Bearingmentioning
confidence: 99%
See 2 more Smart Citations
“…654 In cases of narrowed and functionally incompetent intervertebral discs, less body weight is supported by the disc and forces are consequentially transmitted across the facet joints, 654 reflected in the observation that up to 70% of an axial load can be borne by the facet joints in cases of severe LDDD (thus predisposing to facet arthrosis). 655 Biomechanical studies have suggested that LTDR using ball-and-socket-type LADs (such as the ProDisc-L) results in increased facet loading at the surgical level, 624 especially following L4-L5 and L5-S1 LAD implantation, 590 and these observed increases in facet loading are more evident during lateral bending and axial rotation; and that posterior placement of the prosthesis provides a more physiologic load transfer to the vertebral body.…”
mentioning
confidence: 99%